ChemInform Abstract: One‐Step Synthesis of 2‐Chloropyrimidin‐4‐ol Derivatives: An Unusual Reactivity of Thiophosgene. Issue 8 (February 2016) - Callingham, Michael; Blum, Francesca; Pave, Gregoire
Abstract: The reaction of 2‐aminobenzamides (IV) with thiophosgene leads to 2‐chloropyrimidin‐4‐ol derivatives, which are converted without purification into 2‐morpholine derivatives (VI).